2017
DOI: 10.21149/8204
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and waist circumference of Latin American adult athletes with intellectual disability

Abstract: Objectives. To examine both body mass index (BMI) status and waist circunference (WC) in a large international sample of adult Special Olympics participants from Latin America. It also explored the association of age and sex with obesity in this population. Materials and methods. BMI and WC records from a total of 4 174 (2 683 male and 1 491 female) participant records from the Special Olympics International Health Promotion database were examined. Results. The prevalence of overweight and obesity was quite hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
2
8
1
Order By: Relevance
“…The younger participants with ID had lower BMIs and greater cardiorespiratory endurance and greater flexibility compared to the older participants. These findings are similar to those of research indicating that age unfavorably affects the BMI [44], cardiovascular endurance, and flexibility of adults with ID [45]. However, no effect on muscular strength and endurance was observed in the present study, which contradicts a longitudi-nal study indicating a significant age-related decline in abdominal muscular strength and endurance over a period of 13 years in middle-aged adults (mean age 41.2 ± 9.72 years) with an ID [45].…”
Section: Gender Age and Id Level Differences In Physical Fitness Measuressupporting
confidence: 90%
“…The younger participants with ID had lower BMIs and greater cardiorespiratory endurance and greater flexibility compared to the older participants. These findings are similar to those of research indicating that age unfavorably affects the BMI [44], cardiovascular endurance, and flexibility of adults with ID [45]. However, no effect on muscular strength and endurance was observed in the present study, which contradicts a longitudi-nal study indicating a significant age-related decline in abdominal muscular strength and endurance over a period of 13 years in middle-aged adults (mean age 41.2 ± 9.72 years) with an ID [45].…”
Section: Gender Age and Id Level Differences In Physical Fitness Measuressupporting
confidence: 90%
“…Several studies in the literature report a high incidence of sedentary behavior in people with ID [ 3 , 4 ]. On the other hand, the health risks in these individuals increase when compared to the general population, namely in the higher prevalence of hypertension, obesity, and metabolic syndrome [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A further Irish study by McGuire et al (2007) reported 68% of people with ID to be overweight/obese. Foley et al (2017) examined body mass index (BMI) and waist circumference records from 4174 (2683 men and 1491 women) Latin American Special Olympic athletes demonstrating a significant difference in prevalence, with overweight/obesity (BMI ≥ 25) appreciably higher in women than men (49% vs. 40.8%) and waist circumference measures (≥90 cm in men and ≥94 cm in women) indicating 24.4% prevalence for women and 19.6% in men. Kinnear et al (2018) examined the prevalence of multi-morbidity in people with ID involving over 1000 participants aged 16 years and older and cited obesity as the second most prevalent of 20 dominant conditions (40.6%) but the most dominant condition for people with Down syndrome (56.5%).…”
Section: Introductionmentioning
confidence: 99%